Formation of Marhabat Baigut’s creative way - Tagudretova Б.Б.; Alpysbayev Қ.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article examines Marhabat Baigut’s author’s position, credo, artistic goals, creative environment, literary process and personality. The influence of the classics of Kazakh and Russian literature on the creative path of the writer is considered. The writer’s prose in Kazakh literature is evaluated. Also in overview is given the stages of the emergence, formation and development of the writer’s personality, the main features of his style and skill. Conclusions about the creative biography and about the author-artist M. Baigut is based not only on the analysis of the applicant, but also on the opinions and conclusions of the older generation of writers, critics, literary critics. The writing skills and the writer’s contribution to Kazakh prose were particularly noted. Along with his writing activity, his work as a well-known journalist is appreciated. The creativity of M. Baigut is considered and given as integrity and its evolutionary image. The close connection between the biographical author and the author’s skill shown in the work is shown, its driving mechanisms are differentiated. In particular, life experience, careful observation, rereading world classics, memorizing, if necessary, observing native nature, if possible, immersion in rural life, memories from one’s own experience, daily communication with writers, participation in various spheres of public life, attracting journalistic experience in artistic creativity. Priority is given to artistic results, skills and target skills.